System dynamic modeling of urban carbon emissions based on the regional National Economy and Social Development Plan: A case study of Shanghai city. (20th January 2018) - Du, Lili; Li, Xianzhe; Zhao, Haijun; Ma, Weichun; Jiang, Ping
Abstract: Urban activities are the primary source of carbon emissions. With the accelerating development of urbanization, cities are now facing the dual pressures of maintaining economic growth and reducing carbon emissions, and mega-cities like Shanghai play a crucial role in emission reduction. An integrated system dynamic model (including eight sub-models, which are socio-economic; primary, secondary, and tertiary industry; residential; transportation; waste disposal; and electricity models) is developed using the Vensim platform for evaluating carbon emission trends in Shanghai during 1991–2015, from the perspective of an urban planning system. The results show a general increasing trend in total carbon emissions that reached 245.78 million tons CO2 -equivalent (Mt CO2 -eq) in 2015, which is nearly three times as much as that in 1991. This study also shows that the electric power sector is the main contributor to carbon emissions. Five emission-reduction scenarios were generated by inputting values of planning indicators from the National Economy and Social Development Plan (NESDP) that have direct and indirect impacts on carbon emissions. According to the results of this analysis, the lowest level of carbon emissions is from a scenario with slower socio-economic development and reinforced electrical and industrial energy efficiency programs (Scenario IV), which demonstrates that the appropriate control of energy consumption from secondary industry (especially the electricity sector) will play a positive role in carbon emission mitigation in Shanghai. Outcomes of this study can provide essential information for policy-makers to advance Shanghai's future low-carbon development. These outcomes could also guide similar studies modeling CO2 emissions from the perspective of urban planning systems.